Radiological Outcome of Percutaneous Herbert Screw Fixation in the Treatment of Delayed Union and Nonunion of the Scaphoid - Sardar Sohail Afsar, Akbar Ali, Yaqoob Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: After distal radius fractures, scaphoid fractures are the most prevalent kind of wrist fracture. Scaphoid fractures account for between 60 and 70 percent of all wrist fractures. Different treatment methods are used for their management. Objective: To determine the radiological outcome of percutaneous Herbert screw fixation in the treatment of delayed union and nonunion of the Scaphoid Methodology: The current study was descriptive study carried out at the orthopedic department, Qazi Hussain Ahmad Medical College, Nowshera from November 2021 to November 2022. All the relevant laboratory and radiological investigations were carried out for the enrolled patients. Under general anesthesia all the surgeries were performed. All the patients were followed up until union occurs. IBM SPSS version 23 was employed for analysis of data. Results: In our study, totally 40 patients were included. The male participants in our study were 32 (80%) whereas female participants were 8 (20%). The mean age of the patients was 27 (±4.7) years. The radiological union was achieved in all of our patients in 15.2 (±3.15) weeks. In Delayed union of scaphoid fracture patients the radiological union was achieved in 11 (±3.17) weeks while in nonunion scaphoid fracture patients, it was achieved in 19 (±4.32) weeks. Functional level was achieved in all the patients in 17 (±2.4) weeks. Based on postoperative complications, wrist stiffness was observed in 10 (25%) patients while osteoarthritis and osteonecrosis was not reported in any of our patients. Conclusion: Our study concludes that scaphoid fractures are effectively and conveniently treated by using Percutaneous Herbert screw fixations, which provides satisfactory functional and radiological result with few complications. We suggest the adoption of the Herbert screw for the treatment of scaphoid fractures in our hospital, regardless of whether the fracture has delayed union or is non-union, in order to achieve better radiological and functional outcomes. Keywords: Radiological outcome; percutaneous Herbert screw fixation; delayed union; nonunion